Mapping Social Responsibility Theory in Media and Journalism: A Bibliometric Analysis (2001–2025) - Sakhidad Mahdiyar; Göktürk Yıldız (Yayasan Lentera Avanya Nagari, 2026)
This study examines the intellectual structure and evolving trajectory of Social Responsibility Theory (SRT) within media and journalism studies through a bibliometric analysis of peer-reviewed journal articles published between 2001 and 2025. Drawing on data (n = 54) retrieved from the Scopus database , the analysis employs VOSviewer to map co-authorship networks, keyword co-occurrence patterns, co-citation relationships, and bibliographic coupling structures. The findings reveal a highly fragmented and weakly connected research landscape, characterized by limited scholarly collaboration, low cross-national citation exchange, and the absence of a cohesive theoretical core. While earlier studies are anchored in normative concerns such as ethics, accountability, and democracy, more recent research reflects a shift toward digital-era issues, including misinformation, social media, and platform governance. However, this thematic expansion appears to be reactive rather than theoretically integrative, with SRT functioning more as a residual normative reference than as a dynamic framework. Overall, the results suggest that SRT occupies an increasingly peripheral position in contemporary media scholarship, raising critical questions about its adaptability to the complexities of the digital communication environment. By providing a systematic mapping of the field, this study contributes to ongoing debates on the relevance and future of normative media theories in a rapidly transforming media ecosystem.